Electoral Cycles in Active Labor Market Policies - Mario Mechtel; Niklas Potrafke (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
We examine how electoral motives influence active labor market policies that promote job-creation. Such policies reduce unemployment statistics. Using German state data for the period 1985 to 2004, we show that election-motivated politicians pushed job-promotion schemes before elections.
urn:nbn:de:bsz:21-opus-55939
Keywords: P16; J08; H72; E62; H61; 330; political business cycles; opportunistic politicians; active labor market policies